Utility Evaluation of Information from YouTube on Breastfeeding for Preterm Babies - Chae-Ku Jo; Sun-Young Lee; Myo-Jing Kim (Korean Society of Neonatology, 2019)
Purpose Many studies have reported the merits of breastfeeding, and increasing efforts are made to encourage breastfeeding for preterm babies. Recently, YouTube is being increasingly used as a source of medical information. We evaluated the quality of information provided on YouTube on breastfeeding for preterm babies. Methods On June 20, 2018, we performed a YouTube search using four terms related to breastfeeding for preterm babies. Of the 355 videos in the first five pages, 78 were analyzed; videos with irrelevant content (n=200), duplicated material (n=71), and those using another (non-Korean) language (n=6) were excluded. Videos were classified according to upload source and usefulness, and were evaluated based on reliability and quality. Results Medical websites or TV channels (46.2%) and physicians or hospitals (12.8%) were the most and least common upload sources, respectively. The usefulness of the information was rated the highest in physician or hospital-uploaded videos (70.0%). The reliability of the physician or hospital-uploaded (2.70±1.42) and medical website or TV channel-uploaded (2.91±1.42) videos were statistically significant. The highest proportion of good quality videos (≥good) (60.0%) comprised physician or hospital-uploaded videos. Of the videos evaluated, 44.9% were useful. The highest proportion of useful videos comprised those uploaded by medical websites or TV channels (68.6%). The highest proportion of non-useful videos comprised civilian videos (80.8%). Conclusion Physician or hospital-uploaded videos were more useful and had excellent reliability and quality; however, these had the least amount of information. Development of educational programs by experts that can be accessed by public through popular platforms like YouTube is necessary.